Effects of Microplastics on Immune Responses of the Yellow Catfish Pelteobagrus fulvidraco Under Hypoxia - Li, Li'ang; Xu, Ran; Jiang, Lingfeng; Xu, Elvis Genbo; Wang, Man; Wang, Jie; Li, Bo; Hu, Menghong; Zhang, Lei; Wang, Youji (Frontiers in Physiology, 2021)
Compared with marine organisms, research on microplastics (MPs) in freshwater organisms is still less although MPs have been widely found in freshwater ecosystem. Hypoxia is a ubiquitous issue in freshwater aquaculture, under such scenarios, the toxic effects of MPs on typical aquaculture fish need to be clarified. Here, we studied the effects of MPs (polystyrene) on specific growth rate (SGR), hypoxia inducible factor-1α (HIF-1α), tumor necrosis factor-α (TNF-α), interleukin-8 (IL-8) and interferon (IFN) in the yellow catfish (Pelteobagrus fulvidraco) under hypoxic conditions. After 15 days of exposure, the SGR were not affected by MPs or hypoxia. MPs significantly increased the expressions of HIF-1α and TNF-α, but inhibited the expression of IFN at high concentration MPs under normoxia. However, hypoxia significantly inhibited the expression of IL-8 and TNF-α under high MPs concentration and low MPs concentration, respectively. In addition, MPs had significant concentration-dependent inhibitory effects on IFN under hypoxia. Surprisingly, a positive correction between HIF-1α and TNF-α was found in fish. Although hypoxia might alleviate the effects of MPs with low concentrations, the interaction of hypoxia and MPs aggravated the negative effects of MPs on immune factors at high concentration MPs. This study provided a new insight into the complex effects of hypoxia and microplastics on aquatic organisms, and future work should focus on the cellular pathways of immune cells in fish. Given that MPs could induce the immune response in fish, considerations should be paid to the impacts of MPs on freshwater aquaculture, and hypoxia should be taken into consideration when evaluating the effects of MPs.